Addressing cascading effects of earthquakes in urban areas from network perspective to improve disaster mitigation. (April 2019) - Tang, Pan; Xia, Qi; Wang, Yueyao
Abstract: Given the rising size and complexity of urban areas, the city governments are faced to the challenges of cascading effects triggered by devastating earthquakes, in which the disastrous consequences are amplified significantly by combined effects of the occurred secondary events with interrelationships on the elements at risks. As a low-probability and high impact natural disaster, the escalation of secondary events are guided by the vulnerability paths, as well as their interconnections should be considered from system perspectives during the preparedness and mitigation process. This research aims to develop, model and analyze cascading effects scenario of earthquakes in urban areas for supporting decision making in disaster risk reduction. A framework for addressing cascading effects of earthquakes in urban area is presented. The procedure for developing cascading effects scenario of such highly complex and uncertain disasters by identifying the triggered disaster chains is introduced. A directed network was built to model and visualize the secondary events with interrelationships involving in the cascading effects scenario. In particular, a range of network metrics are developed to examine the relational patterns of hazardous events based on Social Network Analysis. Together with, how to design disaster mitigation strategies according to network analysis results is introduced, such as disaster chains with priorities to be blocked, hazardous events to be mitigated firstly, and essential collaborative relationships among the responsible organizations. Furthermore, a case study in an urban area in Shenzhen City, China was conducted to highlight the application of the proposed framework. This research presents an innovative approach to address cascading effects in urban areas of earthquakes by developing the triggered worst case scenario, as well as understanding secondary events with interrelationships using network analysis method for providing insights to design disaster mitigation strategies from system thinking perspectives.